Radio Geometric Mean Labeling of Some Star Like Graphs - Hemalatha, V.; Mohanaselvi, V.; Amuthavalli, K. (Journal of Informatics and Mathematical Sciences, 2017)
A radio Geometric Mean Labeling of a connected graph \(G\) is a one to one map \(f\) from the vertex set \(V(G)\) to the set of natural numbers \(N\) such that for two distinct vertices \(u\) and \(v\) of \(G\), \(d(u,v)+f(u)f(v) ceil 1+diam(G)\). The radio geometric mean number of \(f, r_gmn (f)\) is the maximum number assigned to any vertex of \(G\). The radio geometric mean number of \(G\), \(r_gmn (G)\) is the minimum value of \(r_gmn (f)\) taken over all radio geometric mean labeling \(f\) of \(G\). In this paper, we find the radio geometric mean number of some star like graphs.